Use of intramuscular triamcinolone acetonide in intermediate responders to janus kinase inhibition for alopecia areata: Case report - Erinolaoluwa F Araoye; Crystal Aguh (Wolters Kluwer Medknow Publications, 2021)
Janus kinase (JAK) inhibitors have been identified as an effective treatment option for severe alopecia areata (AA), but response is variable among patients. Intramuscular triamcinolone acetonide (IMTA), which has a greater bioavailability than other forms of steroids, has been used effectively to treat refractory AA with very few side effects. However, the use of IMTA in combination with JAK inhibitors is not well characterized. We present two patients with severe patch type AA and alopecia totalis who failed to achieve substantial regrowth after at least 6 months of oral tofacitinib and were treated with a single dose of IMTA 60 mg. Both patients had more than 50% increase in hair regrowth in areas of hair loss that had persisted on tofacitinib with no reported adverse effects.